THE EFFECT OF CULTURAL DIVERSITY AND DIGITALIZATION ON THE STUDENT’S CHARACTER, SCIENTIFIC REASONING SKILL, AND RELIGIOUS TOLERANCE IN PESANTREN - Saparudin, Hery; Susanti, Siti Saodah; Mustopa, Azizuddin (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: In an increasingly globalized and digital world, understanding how cultural diversity and digitalization impact students is crucial for fostering well-rounded individuals. Purpose: This study explores the effect of cultural diversity and digitalization on the character, scientific reasoning skills, and religious tolerance of students in pesantren. Method: Using a quantitative approach with Structural Equation Modeling (SEM) assisted by SmartPLS, the research examines the correlations between these variables. Result: The findings reveal that both cultural diversity and digitalization significantly enhance students' character, reasoning abilities, and tolerance towards religious differences. Cultural diversity fosters empathy and respect, while digitalization improves access to information, thereby enriching scientific reasoning. Conclusion: This research highlights the importance of integrating cultural diversity and digitalization into educational strategies to cultivate well-rounded, tolerant, and intellectually capable students.